PENGARUH MODEL CONCEPT SENTENCE TERHADAP KEMAMPUAN SISWA KELAS V SD NEGERI 187 PALEMBANG MENENTUKAN ISI CERITA RAKYAT ASAL MULA TERJADINYA POHON ENAU KARYA SALIM - Rahmadiani; Wahidy, Achmad (Universitas PGRI Palembang, 2022)
This study identified and described the effect of the concept sentence model on the ability of fifth grade students at SD Negeri 187 Palembang to determine the content of the folk tale The Origin of the Palm Tree by Salim. The population of this study only consisted of fifth grade students at SD Negeri 187 Palembang, namely a maximum of 60 with a sample population of 60. The method used in this study was a quasi-experimental method using a group experimental design and a control group. Research data were obtained through test techniques, questionnaires and interviews and were analyzed using test data analysis techniques, questionnaire data analysis and interview data analysis techniques. contents of the folklore The Origin of the Palm Tree by Salim because it proved to be greater than